On the Scope of Quantifying Words - Pilka, Alfonsas (Kalbotyra, 1987)
The central problem under discussion in the article is that of scope of English quantifiers. The term “scope” in linguistics appeared as an extension of its use in formal languages motivated by the existence of phenomena in natural languages that parallel the scope relationship of formal languages. But the scope principles in natural languages are more complex than the simple linear left to right ordering of logical operators in the predicate calculus. The semantics or quantifiers in the English language (or in any other language) is determined by many factors: the inherent properties of the words themselves (they may differ from one another in their preferred scope orders with respect to other operators), their grammatical function and place in the sentence, their presence in the principal or a subordinate clause, (logical) stress, the thematic-rhematic structure of the sentence, etc.